GAMBARAN LINGKUNGAN KERJA SOSIAL, PENGHARGAAN FINANSIAL DAN RETENSI KARYAWAN PADA PT. BAETT MAL ABADI DI CILEGON - Mayasari, Rizka; Senen, Syamsul Hadi; Tarmedi, Eded (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - The purpose of this study is to see the description of social work environment, financial reward and employee retentionDesign/methodology/approachh - The design of this study was cross sectional. This research uses descriptive approach with explanatory survey method. A total of 86 respondents were selected using probability sampling. A questionnaire was used as a research instrument to collect data from respondents. Analytical technique used is descriptive technique by using frequency tableFindings - Based on the results of the research using descriptive analysis, the results obtained that the social work environment is in the good category with a score of respectively 79%, financial reward is in the good category with a score of respectively 78%, employee retention is in the high category with a score of respectively 80%Originality/value -Â This study provides a basis for understanding social work environment issues, financial reward, employee retention. The difference of this study with previous research is focused on the social work environment, financial rewards.